2017
DOI: 10.3892/br.2017.1023
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of selegiline on rat neural stem cells treated with hydrogen peroxide

Abstract: Abstract. Oxidative stress and reactive oxygen species generation have been implicated in the pathogenesis of several neurological disorders including Parkinson's disease, Alzheimer's disease, amyotrophic lateral sclerosis and multiple sclerosis. In the present study, the neuroprotective effects of selegiline against hydrogen peroxide-induced oxidative stress in hippocampus-derived neural stem cells (NSCs) were evaluated. NSCs isolated from neonatal Wistar rats were pretreated with different doses of selegilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Some data show monoamine oxidase inhibitors (MAOI) have pleiotropic effects that are not well defined ( Kitani et al., 2001 ; Szoko et al., 2018 ) and which may be unrelated to monoamine oxidase inhibition ( Koutsilieri et al., 1996 ; Kragten et al., 1998 ; Lieb, 1983 ; Nagatsu and Sawada, 2006 ; Ryu et al., 2018 ; Tabakman et al., 2004 ; Tatton et al., 1994 ). In animal models, these overlapping effects include regulation of inflammation and reactive oxygen species (ROS) ( Bekesi et al., 2012 ; Bielecka et al., 2010 ; Morsali et al., 2013 ; Nagy et al., 2018 ; Tsao et al., 2014 ), alterations in gene expression ( Tatton and Chalmers-Redman, 1996 ; Tatton et al., 1996 ), increasing longevity ( Kitani et al., 1994 , 1998 ; Knoll and Miklya, 2016 ), and promoting neurite outgrowth and neuronal survival ( Abdanipour et al., 2018 ; Ebadi et al., 2002 ; Koutsilieri et al., 1994 ; Kragten et al., 1998 ; Morsali et al., 2013 ; Tazik et al., 2009 ). In the rodent heart, inhibiting monoamine oxidases reduces inflammation and endothelial dysfunction in the aorta ( Ratiu et al., 2018 ; Sturza et al., 2013 ), decreasing ROS and preventing mitochondrial dysfunction and ER stress in diabetic cardiomyopathy ( Deshwal et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some data show monoamine oxidase inhibitors (MAOI) have pleiotropic effects that are not well defined ( Kitani et al., 2001 ; Szoko et al., 2018 ) and which may be unrelated to monoamine oxidase inhibition ( Koutsilieri et al., 1996 ; Kragten et al., 1998 ; Lieb, 1983 ; Nagatsu and Sawada, 2006 ; Ryu et al., 2018 ; Tabakman et al., 2004 ; Tatton et al., 1994 ). In animal models, these overlapping effects include regulation of inflammation and reactive oxygen species (ROS) ( Bekesi et al., 2012 ; Bielecka et al., 2010 ; Morsali et al., 2013 ; Nagy et al., 2018 ; Tsao et al., 2014 ), alterations in gene expression ( Tatton and Chalmers-Redman, 1996 ; Tatton et al., 1996 ), increasing longevity ( Kitani et al., 1994 , 1998 ; Knoll and Miklya, 2016 ), and promoting neurite outgrowth and neuronal survival ( Abdanipour et al., 2018 ; Ebadi et al., 2002 ; Koutsilieri et al., 1994 ; Kragten et al., 1998 ; Morsali et al., 2013 ; Tazik et al., 2009 ). In the rodent heart, inhibiting monoamine oxidases reduces inflammation and endothelial dysfunction in the aorta ( Ratiu et al., 2018 ; Sturza et al., 2013 ), decreasing ROS and preventing mitochondrial dysfunction and ER stress in diabetic cardiomyopathy ( Deshwal et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock proteins broadly function to remove misfolded proteins, but the function of HSPA4 in neurons is not well described. However, in rat neural stem cells, HSPA4 is upregulated by selegiline, a type B monoamine oxidase inhibitor used to treat PD, a process that reduces ROS levels and mitochondrial DNA damage following hydrogen peroxide exposure ( 65, 66 ). In MPTP-treated mice, deacetylation of HSPA4 is linked to decreased microglial activation and neuroinflammation ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 has widely been used to induce cellular oxidative stress in different cell lines. Previous studies have revealed that cultured NSCs are sensitive to the oxidative stress induced by H 2 O 2 [ 48 , 49 , 50 , 51 , 52 ]. In this study, the activity of antioxidant enzymes (GSH-Px and SOD) and the content of GSH in NSCs reduced after treatment with H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%